Reforming proceeds of crime legislation: Political reality or pipedream?. (September 2019) - Skead, Natalie; Tulich, Tamara; Murray, Sarah; Tubex, Hilde
In recent decades, Australian states and territories have introduced a raft of legislation aimed at stripping those involved in criminal activity of their ill-gotten gains. However, in doing so, this far-reaching legislation has the potential to undermine legal principles and protections. We recently completed a study into proceeds of crime legislation in Western Australia, New South Wales and Queensland. From our findings it is clear that Western Australia's legislation is the most far-reaching and potentially the most inequitable. In this article, we provide a critique of Western Australia's legislation informed by our research, and identify pressing areas for reform.